Vast applications of botulinum neurotoxin in neurology - systematic review - Banach, Aleksandra; Grzech, Patrycja; Borowska-Łygan, Martyna; Kreczyńska, Lena Maria; Zubrzycka, Weronika Emilia; Harnicki, Patryk; Ożóg, Weronika; Piskorowska, Klaudia (Journal of Education, Health and Sport, 2025)
Introduction and aim: Botulinum neurotoxin (BoNT), a protein naturally produced by bacteria from the Clostridium family, has evolved into a cornerstone therapy in neurology. The aim of this article is to examine the clinical applications, safety profiles and emerging applications of BoTN in neurology. Review methods: This review is based on publicly avalible PubMed, MDPI and Google Scholar databases, targeting studies published between January 2019 and March 2025. Search terms included “botulinum toxin in neurology”, “BoNT-A in spasticity,” “chronic migraine,” “neuropathic pain treatment” “dystonia treatment”, “hemifacial spasm treatment” and “BoNT-A/B”. Brief description of the state of the art: Through its mechanism of action—blocking acetylcholine release by cleaving SNARE proteins—BoNT enables localized and reversible neuromuscular blockade. Upon oral ingestion, BoNT causes the neuroparalytic syndrome botulism, but BoNT injections are used to manage chronic medical conditions across multiple indications. Since its first therapeutic use in the 1980s, BoNT has been widely adopted for medical and cosmetic applications. In addition to its established role in treating hyperkinetic movement disorders such as dystonia and spasticity, BoNT has demonstrated significant effectiveness in managing a range of autonomic nervous system disorders. Especially serotyoes A and B are utilized, showing both safety and efficacy. Summary: Applications of botulinum toxin have demonstrated continued growth in therapeutic scope, reinforcing its value across neurology. With the accumulation of clinical evidence and technological advancements, BoNT’s role is constantly expanding and offering targeted relief with minimal systemic effects.